Plasma intestinal alkaline phosphatase and intermediate molecular mass gamma glutamyltransferase activities in the differential diagnosis of jaundice. Issue 10 (October 1987) - Collins, D; Goold, M F; Rosalki, S B; Mayne, P D; Foo, A Y
Abstract : An assessment was made of the value of: (i) the demonstration of intestinal alkaline phosphatase in plasma for the differentiation of intrahepatic from post-hepatic jaundice in 122 jaundiced patients; and (ii) the demonstration of an intermediate molecular mass gamma glutamyltransferase in plasma for the identification of post-hepatic cholestasis in 74 jaundiced patients. The first test had a diagnostic sensitivity of only 32% with a specificity of 86%; the second test had a sensitivity of 50% and specificity of 75%. It is concluded that neither procedure is worth while.